Projecting cardiovascular deaths averted due to trans fat policies in the Eurasian Economic Union - Matthias Rieger; Holly L Rippin; Adriana Pinedo; Stephen Whiting; Clare Farrand; Kremlin Wickramasinghe; Joao J Breda (Cambridge University Press, 2023)
Abstract Objective: To demonstrate the potential impact on population health if policies designed to reduce population trans fatty acid (TFA) intake are successfully implemented in the Eurasian Economic Union (EAEU) in line with the WHO's guidelines to lower intake of TFA as a percentage of total energy intake to less than 1 %. Design: A projection exercise was conducted to estimate reductions in CVD-related deaths in countries of the EAEU if TFA policies are implemented in the EAEU. Plausibly causal, annual effects (in %) of Denmark's TFA policy on the evolution of CVD mortality rates were applied to project the potential effects of recently announced TFA policies in Armenia, Belarus, Kazakhstan, Kyrgyzstan and the Russian Federation under three TFA exposure scenarios. Settings: Member States of the EAEU: Armenia, Belarus, Kazakhstan, Kyrgyzstan and the Russian Federation. Participants: Data used for the projection exercise were based on estimates from natural experimental evidence from Denmark. National CVD mortality rates used were from WHO and the Organisation for Economic Cooperation and Development datasets. Results: In all countries and in all scenarios, deaths averted were ≤ 5 deaths/100,000 in year 1 and rose in years 2 and 3. The highest projected impacts in the high-exposure scenario were seen in Kyrgyzstan (39 deaths/100 000), with the lowest occurring in Armenia (24 deaths/100 000). Conclusion: This study demonstrates the potential population health gains that can be derived from effective policies to reduce TFA in line with WHO guidance. Monitoring and surveillance systems are needed to evaluate the effectiveness of the TFA reduction policies in a national context.